(untitled) (Innovaciones Educativas, 2025)
The COVID-19 pandemic demonstrated the need to incorporate digital platforms into the teaching and learning process in order to guarantee the continuity of academic training. Based on this reality, the Universidad Estatal a Distancia de Costa Rica opted for an online modality to cope with the new situation. This process has been a challenge for the faculty, which has had to rethink teaching strategies in virtual learning environments, in line with the pedagogical model of the university and distance education. In view of this, research with qualitative approach and phenomenological design was proposed to analyze how the faculty of the Chair of Preschool Child Development has managed to incorporate active methodologies in their pedagogical and media practice. The results showed that teachers have approached active methodologies such as project-based and problem-based learning, case studies and cooperative learning through the didactic strategies implemented in this chair. However, it is necessary to promote training spaces related to this topic to fill some gaps in the planning, implementation and evaluation of these methodologies in virtual learning environments.